2020
DOI: 10.1166/jctn.2020.8906
|View full text |Cite
|
Sign up to set email alerts
|

Improving Scalability and Balancing the Network Load Using Adaptive Multiparent Crossover Method in Wireless Sensor Networks

Abstract: Wireless sensor network comprises of scattered sensors to sense, monitor and aggregate the sensed information. The major issue in a wireless sensor network is to balance network load and to maintain less energy consumption where multi parent crossover method is considered. Multiparent cross over method will generate offspring from parent and aims at managing the load. In this paper a comparative study of different algorithms is done where the load balancing and energy consumption issue has been resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Te cost efectiveness and efcient system utilization improve the overall system's performance. Spatharakis et al [66] suggested the QoS-aware load balancing of cloudlets in WMAN with two efective techniques for distributing the workload across cloudlets to reduce the maximum task response time [68]. Experimental simulation results showed that the proposed methods performed well and showed promise.…”
Section: Mobile Information Systemsmentioning
confidence: 99%
“…Te cost efectiveness and efcient system utilization improve the overall system's performance. Spatharakis et al [66] suggested the QoS-aware load balancing of cloudlets in WMAN with two efective techniques for distributing the workload across cloudlets to reduce the maximum task response time [68]. Experimental simulation results showed that the proposed methods performed well and showed promise.…”
Section: Mobile Information Systemsmentioning
confidence: 99%